A Critical Analysis of Possible Natural Disasters in the Himalayan Region and a Detailed Study of the Consequences Thereof - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (Integrated Journal for Research in Arts and Humanities, 2022)
The Himalayan Mountainous region is the world's newest, fastest, and most enormous crumpled mountainous range. It is highly volatile because of the continuous geological process. The entire Himalayas range has been responding to devastating natural hazards, which reflects its fragility and susceptibility. The temperature ranges from low-lying hills and mountains to high-altitude, continuously snow-capped mountainous ranges. According to studies, the temperature revolution had a profound effect on the Mountains, and as a result, weather patterns and disasters have changed substantially. The Mountainous terrain's high frequency magnifies weather hazards, bringing everyone else in the area at risk. Humans are no strangers to disasters. Since the beginning of civilization, they have been persistent, though unpleasant, companions of humans, leaving trails of rage and disaster of incredible magnitude. Uttarakhand is susceptible to disasters, glaciers, river flooding, forest fires, cloudbursts, and land degradation, among other disasters.